(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
In this paper we have examined the screening effects of weak Debye plasma on elastic scattering of electrons (e"’) or positrons (e+) by atomic as well molecular hydrogen at intermediate and high incident energies Ei â‰¥50 eV. The present theoretical work aims at investigating how plasma influences the angular and total scattering, in the background of free or no-plasma situation. The basic calculations are carried out in the ’eikonal-Born-series’ (EBS) approach suitable for atomic hydrogen, along with the ’Independent Atom-in-Molecule’ (IAiM) model for the H2 molecular target. Debye screening length Î›D is adopted as the parameter to assess the effect of the plasma environment on the scattering. Reduction in the forward differential cross sections (FDCS) and the total (complete) cross sections (TCS) is studied at typical values Î›D = 5, 7.5 and 10 Bohr radii a0. Our results show that, compared to the TCS, the FDCS are more sensitive to the plasma effects, for both H and H2 targets. Further for both these targets, differences between electron and positron scattering are also observed in our theoretical results.